Long‐term consequences of breastfeeding on cholesterol, obesity, systolic blood pressure and type 2 diabetes: a systematic review and meta‐analysis. (December 2015) - Horta, Bernardo L.; Loret de Mola, Christian; Victora, Cesar G.
Abstract: Aim: To systematically review the evidence on the associations between breastfeeding and overweight/obesity, blood pressure, total cholesterol and type 2 diabetes. Methods: Two independent literature searches were carried out using the MEDLINE, LILACS, SCIELO and Web of Science databases. Studies restricted to infants and those without an internal comparison group were excluded. Fixed‐ and random‐effects models were used to pool the estimates. Results: Breastfed subjects were less likely to be considered obese/overweight [pooled odds ratio: 0.74 (95% confidence interval (CI): 0.70; 0.78)] (n = 113). Among the 11 high‐quality studies, the association was smaller [pooled odds ratio: 0.87 (95%CI: 0.76; 0.99)]. Total cholesterol (n = 46) was independent of breastfeeding [pooled mean difference: −0.01 mmol/L (95%CI: −0.05; 0.02)]. Systolic blood pressure (n = 43) was lower among breastfed subjects [mean difference: −0.80 (95%CI: −1.17; −0.43)], but no association was observed among larger studies, and for diastolic blood pressure (n = 38) [mean difference: −0.24 (95%CI: −0.50; 0.02)]. For type 2 diabetes (n = 11), the odds ratio was lower among those subjects who had been breastfed [pooled odds ratio: 0.65 (95%CI: 0.49; 0.86)]. Conclusion: Breastfeeding decreased the odds of type 2 diabetes and based on high‐quality studies, decreased by 13% the odds of overweight/obesity. No associations were found for total cholesterol or blood pressure.